2022
DOI: 10.1021/acs.chemmater.2c01673
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Chemical Order and Disorder in High-Entropy MXenes: A High-Throughput Survey of the Atomic Configurations in TiVNbMoC3 and TiVCrMoC3

Abstract: Expanding the MXene design space from ordered and random double-transition-metal (DTM) MXenes to include high-entropy (HE) MXenes with four or more principal elements enables a powerful approach for enhancing MXene properties. While many DTM MXenes possess unique structures that strongly influence material properties, HE MXenes are largely unknown because they are only recently synthesized. Since certain combinations of transition metals (TMs), e.g., Mo-Ti and Cr-Ti, lead to ordered DTM MXene phases, where Mo/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…It is revealed that the interlayer spacing is similarly large and it varies very little with placements of the four transition metal atoms. The energy differences are also small; it is worth mentioning that the first configuration (Figure S1a) with Mo and V (Ti) atoms in the outer (inner) layer has the lowest energy among them, which is consistent with the reported elemental preference, , where the Mo and V atoms prefer to be in the outer layer, while Ti atoms prefer the inner layer. Also, the energy of the configuration with Ti atoms in the outer layer and Mo/V atoms in the inner layer (Figure S1b,c) is relatively higher.…”
Section: Resultssupporting
confidence: 84%
“…It is revealed that the interlayer spacing is similarly large and it varies very little with placements of the four transition metal atoms. The energy differences are also small; it is worth mentioning that the first configuration (Figure S1a) with Mo and V (Ti) atoms in the outer (inner) layer has the lowest energy among them, which is consistent with the reported elemental preference, , where the Mo and V atoms prefer to be in the outer layer, while Ti atoms prefer the inner layer. Also, the energy of the configuration with Ti atoms in the outer layer and Mo/V atoms in the inner layer (Figure S1b,c) is relatively higher.…”
Section: Resultssupporting
confidence: 84%
“…Leong et al calculated the thermostatically stable configurations of TiVNbMoC 3 and TiVCrMoC 3 , and found that the metals showed obvious preferential occupation at high temperatures, with Cr most inclined to the outer layer, followed by Mo. [23] In addition, the metals in high-entropy MAX precursor were in a solid solution state above 1873 K, while Nb and V atoms showed significant separation in the inner layer below 928 K. x observed along the a/b axis. Reproduced with permission.…”
Section: Synthesis Of Mxenesmentioning
confidence: 99%
“…Our previous works on double-ordered MXene nanosheets displayed promising results both computationally and experimentally, , wherein a double transition metal provided more space for Li-ion intercalation, leading to high performance with cyclic stability. Nemani et al, Hong et al, and Leong et al explored the synthetic aspects of double-ordered, high-entropy MXene (HEM) via computational and experimental methods. Du et al have successfully synthesized the HEM containing the transition metals Ti, V, Zr, Nb, and Ta using the classical technique of the MAX phase followed by HCL and LiF etching and used as a Li-ion anode. The high molar concentration and lattice distortions resulted in a high mechanical strain, further aiding the dendrite-free Li on HEM layers.…”
Section: Introductionmentioning
confidence: 99%